Ser or Leu: structural snapshots of mistranslation in Candida albicans - Sárkány, Zsuzsa; Silva, Alexandra; Pereira, Pedro J. B.; Macedo-Ribeiro, Sandra (Frontiers in Molecular Biosciences, 2014)
Candida albicans is a polymorphic opportunistic fungal pathogen normally residing as commensal on mucosal surfaces, skin and gastrointestinal and genitourinary tracts. However, in immunocompromised patients C. albicans can cause superficial mucosal infections or life-threatening disseminated candidemia. A change in physiological conditions triggers a cascade of molecular events leading to morphogenetic alterations and increased resistance to damage induced by host defenses. The complex biology of this human pathogen is reflected in its morphological plasticity and reinforced by the ability to ambiguously translate the universal leucine CUG codon predominantly as serine, but also as leucine. Mistranslation affects more than half of C. albicans proteome and it is widespread across many biological processes. A previous analysis of CTG-codon containing gene products in C. albicans suggested that codon ambiguity subtly shapes protein function and might have a pivotal role in signalling cascades associated with morphological changes and pathogenesis. In this review we further explore this hypothesis by highlighting the role of ambiguous decoding in macromolecular recognition of key effector proteins associated with the regulation of signal transduction cascades and the cell cycle, which are critical processes for C. albicans morphogenic plasticity under a variety of environmental conditions.